Clinical efficacy of weekly cisplatin for treatment of patients with breast cancer. Issue 37 (September 2019) - Ma, Ying; Zhang, Nai-peng; An, Ning; Li, Wen-yuan; Zhao, Wei; Liu, Yan-cui
Abstract: Background: We will investigate the efficacy and safety of weekly cisplatin (WC) for treatment of patients with breast cancer (BC) systematically. Methods: This study will describe and critically appraise shared decision approaches used in randomized controlled trials of WC for treatment of patients with BC. We will comprehensively search the following databases: PubMed, EMBASE, Web of Science, Cochrane Library, CINAHL, PsycINFO, Allied and Complementary Medicine Database, Wanfang, and Chinese Biomedical Literature Database from inception through July 1, 2019. We will utilize RevMan V.5.3 software (London, UK) for statistical analysis. Results: This study will systematically explore the efficacy and safety of WC for the treatment of patients with BC through evaluating primary outcomes of overall survival, pathological complete response; and secondary outcomes of cancer-specific survival, recurrence-free survival, disease-free survival, quality of life, and toxicities. Conclusion: This study will provide latest evidence of WC for the treatment of patients with BC. Systematic review registration: PROSPERO CRD42019145358.